Preparation and application method of gasified slag-based carbon-zeolite composite material
A gasification slag-based carbon-zeolite composite material is prepared through a simple process to simultaneously adsorb ammonia nitrogen and degrade organic matter in wastewater, addressing the limitations of existing methods with improved efficiency and cost-effectiveness.
Patent Information
- Application Number
- CN202411520422.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-03
AI Technical Summary
Existing methods for utilizing gasification slag do not effectively address the simultaneous adsorption of ammonia nitrogen and degradation of organic matter in industrial wastewater, and involve complex processes and high costs.
A method to prepare a gasification slag-based carbon-zeolite composite material by mixing gasified slag with alkali, a silicon source, surfactant, and water, followed by hydrothermal reaction, which controls zeolite morphology and modifies the carbon surface for enhanced adsorption and catalytic degradation.
The composite material achieves high removal rates of ammonia nitrogen and refractory organic matter in wastewater, with recyclability and low preparation costs, providing both economic and environmental benefits.
Smart Images

Figure CN119236881A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon-zeolite composite materials, and in particular to a preparation method and application method of a gasification slag-based carbon-zeolite composite material. Background Art
[0002] Gasification slag is a solid residue formed by the incomplete combustion of coal with oxygen or oxygen-enriched air to generate CO and H2. The inorganic minerals in the coal undergo different physical and chemical transformations and are accompanied by the carbon particles remaining in the coal. It is a carbon ash composite solid waste produced in the modern coal chemical process. Its reserves are huge, and its accumulation and landfill will occupy precious land resources and seriously damage the surrounding geological environment. Therefore, how to realize the resource utilization of gasification slag solid waste to solve the severe ecological problems is an urgent problem to be solved.
[0003] For example, the existing patents CN106336164A and CN106467376A respectively disclose a method for preparing unburned bricks using gasified slag, using gasified slag as raw material, adding cement, bean sand stone or coal gangue and steel slag and other materials to adjust the composition ratio and mix, and obtain unburned brick products after molding-curing. Based on its chemical composition characteristics, CN103936134A discloses a method for treating phenol-containing wastewater using synthetic ammonia gasified slag, after the gasified slag is mixed with dilute alkali sodium hydroxide for reaction, the modified gasified slag is obtained by washing-drying, wherein the adsorption performance of the particle surface and pores is greatly increased, and the removal rate of phenol in the wastewater can reach about 90%. Based on the high carbon content of gasified slag, CN102980195A discloses a method for treating coal chemical gasified slag, after the gasified slag is evenly mixed with coal slime, white mud slurry is added, and it is sent to a fluidized bed boiler through a conveying pipeline for combustion to improve the utilization efficiency of carbon therein.
[0004] However, with the rapid development of industrialization in my country and the improvement of national environmental awareness, the purification and treatment of industrial wastewater has received more and more attention. Many industrial wastewaters contain a large amount of ammonia nitrogen and organic matter, which are harmful to human health. Although the above method improves the resource utilization of gasification slag, it cannot simultaneously improve the adsorption of ammonia nitrogen in wastewater and the degradation of organic matter.
[0005] Chinese patent CN113289578A discloses a gasification slag-based composite ammonia nitrogen adsorbent, its preparation method, regeneration method, and application and treatment method of ammonia nitrogen-containing wastewater. First, the gasification slag is subjected to carbon ash separation to obtain carbon-rich slag; then, the carbon-rich slag, sodium source material and aluminum source material are subjected to hydrothermal reaction under alkaline conditions and in the presence of water to obtain a gasification slag-based composite ammonia nitrogen adsorbent. However, the above method has a complicated processing process and requires the preparation of carbon-rich slag first. Moreover, the material prepared by this method can only be used to adsorb ammonia nitrogen and does not have the function of carbon catalytic degradation of organic matter.
[0006] Therefore, it is of great practical significance to provide an adsorption-catalytic composite functional material with high ammonia nitrogen and organic matter removal rate, low cost, and recyclability, while being able to achieve effective utilization of gasification slag solid waste resources. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a method for preparing and applying a gasification slag-based carbon-zeolite composite material. The method has a simple process and low preparation cost, and at the same time realizes high value-added utilization of gasification slag, achieves the purpose of treating waste with waste, and has both economic and environmental benefits.
[0008] The method for preparing a gasified slag-based carbon-zeolite composite material of the present invention comprises the following steps:
[0009] (1) washing the gasified slag to neutrality and drying it to obtain a dry raw material;
[0010] (2) mixing the gasified slag with alkali, a silicon source material, a surfactant and water to obtain a mixed slurry;
[0011] (3) aging the mixed slurry in step (2), and then placing it in a hydrothermal kettle for hydrothermal reaction;
[0012] (4) After the hydrothermal reaction is completed, the hydrothermal reaction product is washed, solid-liquid separated and dried to obtain the gasification slag-based carbon-zeolite composite material.
[0013] The invention adds a surfactant to control the morphology of zeolite through steric hindrance effect, adjust it into flaky zeolite, and improve the adsorption reaction rate; on the other hand, the functional group of the surfactant is used to modify the carbon surface to improve its performance of catalyzing the degradation of organic matter by persulfate.
[0014] Preferably, the alkali in step (2) is any one of sodium hydroxide and potassium hydroxide; the silicon source material is any one of silica sol and amorphous silicon dioxide; the surfactant is a quaternary ammonium salt surfactant;
[0015] The quaternary ammonium salt surfactant is any one of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide and didecyldimethylammonium bromide.
[0016] Preferably, the ratio of the gasified slag, alkali, silicon source material, surfactant and water in step (2) is 5-6 g: 1-2 g: 5-10 g: 1-5 g: 20-50 mL.
[0017] Preferably, the aging in step (3) is carried out under ultrasonic conditions; the power of the ultrasonic treatment is 20 to 40 kHz; the temperature of the aging treatment is 20-30° C., and the aging time is 2-5 h.
[0018] Preferably, the temperature of the hydrothermal reaction in step (3) is 120-150° C., and the hydrothermal time is 8-28 h.
[0019] Preferably, the washing liquid used in step (4) is distilled water, and the drying temperature is 60-80°C.
[0020] Another object of the present invention is to provide a gasified slag-based carbon-zeolite composite material prepared by the above method, wherein the carbon-zeolite composite material has a particle size of 2 to 5 μm, a pore size of 5.5 to 7.2 nm, and a specific surface area of 65 to 80 m 2 / g.
[0021] The gasification slag-based carbon-zeolite composite material can be regenerated and used. The regeneration method of the gasification slag-based carbon-zeolite composite material comprises the following steps:
[0022] The gasification slag-based carbon-zeolite composite material is immersed in a regeneration solution at 85 to 95° C. for 1 to 3 hours, and a regenerated gasification slag-based carbon-zeolite composite material is obtained after solid-liquid separation and drying;
[0023] The regeneration solution is a saturated sodium chloride solution containing 1-3% of a quaternary ammonium salt surfactant.
[0024] The present invention also provides an application method of a gasification slag-based carbon-zeolite composite material, using the carbon-zeolite composite material to adsorb ammonia nitrogen compounds in wastewater and catalytically degrade refractory organic matter in water. The specific method is:
[0025] 5-10 g / L of gasification slag-based carbon-zeolite composite material is added to wastewater containing ammonia nitrogen and refractory organic matter, and then 1-1.5 g / L of oxidant is added, and adsorption catalysis is carried out at room temperature for 70-90 minutes; the oxidant is sodium persulfate or potassium persulfate.
[0026] Ammonia nitrogen refers to combined nitrogen that exists in the form of ammonia or ammonium ions in water, that is, free ammonia (NH3) and ammonium ions (NH 4+ ) in the form of nitrogen; the refractory organic matter refers to organic matter in water that is difficult to be degraded by biochemical treatment, such as phenol, bisphenol A and other organic matter.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The gasification slag-based carbon-zeolite composite material prepared by the present invention has a good removal effect on low-concentration ammonia nitrogen and difficult-to-degrade organic wastewater. It has a good treatment effect on inorganic-organic composite wastewater containing ammonia nitrogen and difficult-to-degrade organic matter, such as coal chemical wastewater.
[0029] (2) The zeolite morphology in the material prepared by the present invention is controllable, and more flaky zeolites are generated by adding surfactants, the adsorption reaction flux is increased, and the reaction rate of the adsorption process is accelerated; at the same time, the addition of surfactants to modify the carbon makes the carbon surface in the carbon-zeolite composite material have more functional groups, thereby improving its ability to catalyze the degradation of phenol by persulfate. Therefore, the two effects of regulating the zeolite morphology and modifying the carbon are achieved simultaneously in one hydrothermal process by adding surfactants.
[0030] (3) The application mode of the carbon-zeolite composite material of the present invention is different from the direct adsorption of zeolite. Instead, while the zeolite adsorbs ammonia nitrogen, the carbon catalyzes the degradation of organic matter. Therefore, persulfate is added to the wastewater as an oxidant. The basic process is that the carbon catalyzes the persulfate to produce free radicals or non-free radicals. These active species further react with organic matter to achieve the purpose of degrading organic matter. At the same time, the zeolite component adsorbs ammonia nitrogen inorganic ions through ion exchange.
[0031] (2) The gasification slag-based carbon-zeolite composite material prepared by the present invention can be recycled, the regeneration method is simple, and after regeneration, it still has good ammonia nitrogen and difficult-to-degrade organic wastewater removal performance; the specific regeneration method is to use saturated sodium chloride to wash the zeolite for regeneration; at the same time, add a surfactant for washing to modify the surface of the carbon for regeneration. The washing regeneration method of the present invention requires low temperature, is easy to operate, the washing liquid is also recycled, and the effect after regeneration is significant.
[0032] (3) The present invention utilizes gasification slag to prepare gasification slag-based carbon-zeolite composite materials. The process is simple and the preparation cost is low. At the same time, high added value utilization of gasification slag is achieved, achieving the purpose of treating waste with waste, and having both economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The catalytic adsorption performance diagram before and after adding surfactant;
[0034] Figure 2 This is a SEM image of the gasification slag-based adsorption catalytic carbon-zeolite composite material prepared in Example 1;
[0035] Figure 3 This is the SEM image of the composite material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with the embodiments.
[0037] In a specific embodiment of the present invention, the carbon content of the gasified slag is 54wt%, the silicon content is 21wt%, the aluminum content is 11wt%, and the remainder is unnecessary impurities. The specific surface area of the gasified slag is 30-50m 2 ·g -1.
[0038] Example 1
[0039] A method for preparing a gasification slag-based adsorption catalytic carbon-zeolite composite material, comprising the following steps:
[0040] (1) washing the gasified slag to neutrality, drying at 105° C. for 24 h to obtain a dry raw material;
[0041] (2) mixing the gasified slag with sodium hydroxide, silica sol with a mass concentration of 30%, hexadecyltrimethylammonium bromide and water in a ratio of 5 g: 1 g: 5 g: 1 g: 20 mL;
[0042] (3) aging the mixed slurry in step (2) at 20° C. for 2 h under ultrasonic conditions (20 kHz), and then placing it in a hydrothermal kettle for hydrothermal reaction at a temperature of 140° C. for 24 h;
[0043] (4) After the hydrothermal reaction is completed, the hydrothermal reaction product is washed with distilled water until it is neutral, the solid and liquid are separated, and the product is dried at 60° C. to obtain the gasification slag-based adsorption catalytic carbon-zeolite composite material.
[0044] Example 2
[0045] A method for preparing a gasification slag-based adsorption catalytic carbon-zeolite composite material, comprising the following steps:
[0046] (1) washing the gasified slag to neutrality and drying it to obtain a dry raw material;
[0047] (2) mixing the gasified slag with sodium hydroxide, silica sol with a mass concentration of 30%, hexadecyltrimethylammonium bromide and water in a mass ratio of 6 g:2 g:10 g:5 g:50 mL;
[0048] (3) aging the mixed slurry in step (2) at 20° C. for 5 h under ultrasonic conditions (30 kHz), and then placing it in a hydrothermal kettle for hydrothermal reaction at a temperature of 150° C. for 24 h;
[0049] (4) After the hydrothermal reaction is completed, the hydrothermal reaction product is washed with distilled water until it is neutral, the solid and liquid are separated, and the product is dried at 80° C. to obtain the gasification slag-based adsorption catalytic carbon-zeolite composite material.
[0050] Example 3
[0051] A method for preparing a gasification slag-based adsorption catalytic carbon-zeolite composite material, comprising the following steps:
[0052] (1) washing the gasified slag to neutrality and drying it to obtain a dry raw material;
[0053] (2) mixing the gasified slag with sodium hydroxide, silica sol with a mass concentration of 30%, hexadecyltrimethylammonium bromide and water in a mass ratio of 6g:2g:10g:3g:40mL;
[0054] (3) aging the mixed slurry in step (2) at 30° C. for 2 h under ultrasonic conditions (40 kHz), and then placing it in a hydrothermal kettle for hydrothermal reaction at a temperature of 150° C. for 24 h;
[0055] (4) After the hydrothermal reaction is completed, the hydrothermal reaction product is washed with distilled water until it is neutral, the solid and liquid are separated, and the product is dried at 60° C. to obtain the gasification slag-based adsorption catalytic carbon-zeolite composite material.
[0056] Comparative Example 1
[0057] A method for preparing a gasification slag-based adsorption catalytic carbon-zeolite composite material, the steps are the same as those in Example 1, except that cetyltrimethylammonium bromide is not added in step (2) of Comparative Example 1, and the remaining steps are the same as those in Example 1.
[0058] Comparative Example 2
[0059] A method for preparing a gasification slag-based adsorption catalytic carbon-zeolite composite material, the steps are the same as those in Example 1, except that no aging is performed in step (3) of Comparative Example 2, and the remaining steps are the same as those in Example 1.
[0060] Comparative Example 3
[0061] A method for preparing a gasification slag-based adsorption catalytic carbon-zeolite composite material, the steps are the same as those in Example 1, except that the temperature of the hydrothermal reaction in step (3) of Comparative Example 3 is 180°C and the time is 24 hours, and the remaining steps are the same as those in Example 1.
[0062] The performance of the gasification slag-based adsorption catalytic composite functional materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and the results are shown in Table 1:
[0063] Table 1 Property parameters of gasification slag-based carbon-zeolite composites
[0064] <![CDATA[Specific surface area / m 2 ·g -1 > Pore diameter / nm Particle size / μm Example 1 68 5.5 5.00 Example 2 80 7.2 2.20 Example 3 75 6.8 3.60 Comparative Example 1 58 4.8 5.13 Comparative Example 2 50 5.0 5.20 Comparative Example 3 47 5.2 5.58
[0065] Experiment 1
[0066] The gasification slag-based adsorption catalytic carbon-zeolite composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were used to carry out an adsorption experiment, and the specific method was as follows:
[0067] 8 g / L of gasification slag-based adsorption catalytic carbon-zeolite composite material was added to the wastewater containing ammonia nitrogen and organic matter, and then 1.5 g / L of oxidant sodium persulfate was added, and the adsorption catalysis was carried out at room temperature for 80 minutes.
[0068] The wastewater containing ammonia nitrogen and organic matter to be treated includes phenol with a concentration of 50 mg / L and ammonia nitrogen solution with a concentration of 50 mg / L.
[0069] The removal results of different gasification slag-based adsorption catalytic carbon-zeolite composite materials are shown in Table 2:
[0070] Table 2 Removal results of different gasification slag-based adsorption catalytic carbon-zeolite composite materials
[0071] Phenol concentration / mg·L Ammonia nitrogen solution concentration / mg·L Initial concentration 50 50 Example 1 5 11 Example 2 6 12 Example 3 6 12 Comparative Example 1 13 25 Comparative Example 2 13 23 Comparative Example 3 12.5 20
[0072] Experiment 2
[0073] The gasification slag-based adsorption catalytic carbon-zeolite composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were regenerated by the following specific method:
[0074] The gasification slag-based adsorption catalytic composite functional material is immersed in a regeneration solution (a saturated sodium chloride solution containing 1-3% of a quaternary ammonium salt surfactant) at 90° C. for 2 hours, and the regenerated gasification slag-based adsorption catalytic composite functional material is obtained after solid-liquid separation and drying.
[0075] The adsorption experiment was carried out using a regenerated gasification slag-based composite ammonia nitrogen adsorbent, and the specific method was the same as in Experiment 1. The removal results of different regenerated gasification slag-based adsorption catalytic composite functional materials are shown in Table 3:
[0076] Table 3 Removal results of different regenerated gasification slag-based adsorption catalytic composite functional materials
[0077]
[0078]
[0079] Experiment 3
[0080] 8 g / L of the composite material prepared in Example 1 or Comparative Example 1 was added to the wastewater containing ammonia nitrogen and organic matter, and then 1.5 g / L of the oxidant sodium persulfate was added. The wastewater containing ammonia nitrogen and organic matter included 50 mg / L phenol and 50 mg / L ammonia nitrogen solution, and adsorption catalysis was carried out at room temperature for 80 minutes.
[0081] The composite materials prepared in Example 1 and Comparative Example 1 were subjected to catalytic adsorption research, and the performance graphs of the gasification slag-based adsorption catalytic carbon-zeolite composite materials prepared in Example 1 and Comparative Example 1 were obtained as shown in FIG. Figure 1 .
[0082] from Figure 1It can be seen that after the surfactant regulates the adsorption catalytic equilibrium of hydrothermal synthesized carbon-zeolite composite material, phenol remains 10% and ammonia nitrogen remains 22%. After the direct hydrothermal synthesized carbon-zeolite composite material adsorption catalytic equilibrium, phenol remains 26% and ammonia nitrogen remains 50%.
[0083] Experiment 4
[0084] The composite materials prepared in Example 1 and Comparative Example 1 were subjected to SEM analysis, and the SEM images of the gasification slag-based adsorption catalytic carbon-zeolite composite material prepared in Example 1 were obtained as shown in FIG. Figure 2 The SEM image of the composite material prepared in Comparative Example 1 is as follows: Figure 3 .
[0085] from Figure 2 and Figure 3 It can be seen that the carbon-zeolite composite material synthesized by surfactant-regulated hydrothermal synthesis is in the form of flakes, while the carbon-zeolite composite material synthesized by direct hydrothermal synthesis is in the form of spheres.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a gasified slag-based carbon-zeolite composite material, characterized in that: The following steps are involved: (1) washing the gasified slag to neutrality and drying it to obtain a dry raw material; (2) mixing the gasified slag with alkali, a silicon source material, a surfactant and water to obtain a mixed slurry; (3) aging the mixed slurry in step (2), and then placing it in a hydrothermal kettle for hydrothermal reaction; (4) After the hydrothermal reaction is completed, the hydrothermal reaction product is washed, solid-liquid separated and dried to obtain the gasification slag-based carbon-zeolite composite material.
2. The method for preparing the gasified slag-based carbon-zeolite composite material according to claim 1, characterized in that: The alkali in step (2) is any one of sodium hydroxide and potassium hydroxide; the silicon source material is any one of silica sol and amorphous silicon dioxide; the surfactant is a quaternary ammonium salt surfactant; The quaternary ammonium salt surfactant is any one of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide and didecyldimethylammonium bromide.
3. The method for preparing the gasified slag-based carbon-zeolite composite material according to claim 1, characterized in that: The ratio of the gasified slag, alkali, silicon source material, surfactant and water in step (2) is 5-6g: 1-2g: 5-10g: 1-5g: 20-50mL.
4. The method for preparing the gasified slag-based carbon-zeolite composite material according to claim 1, characterized in that: The aging in step (3) is carried out under ultrasonic conditions; the power of the ultrasonic treatment is 20 to 40 kHz; the temperature of the aging treatment is 20 to 30° C., and the aging time is 2 to 5 hours.
5. The method for preparing the gasified slag-based carbon-zeolite composite material according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (3) is 120-150° C., and the hydrothermal time is 8-28 hours.
6. The method for preparing the gasified slag-based carbon-zeolite composite material according to claim 1, characterized in that: The washing liquid used in step (4) is distilled water, and the drying temperature is 60-80°C.
7. A gasification slag-based carbon-zeolite composite material, characterized in that: The carbon-zeolite composite material is prepared by the preparation method according to any one of claims 1 to 6, wherein the particle size of the carbon-zeolite composite material is 2 to 5 μm, the pore size is 5.5 to 7.2 nm, and the specific surface area is 65 to 80 m 2 / g.
8. A method for regenerating the gasification slag-based carbon-zeolite composite material according to claim 7, characterized in that: The following steps are involved: The gasification slag-based carbon-zeolite composite material is immersed in a regeneration solution at 85 to 95° C. for 1 to 3 hours, and a regenerated gasification slag-based carbon-zeolite composite material is obtained after solid-liquid separation and drying; The regeneration solution is a saturated sodium chloride solution containing 1-3% of a quaternary ammonium salt surfactant.
9. A method for applying the gasification slag-based carbon-zeolite composite material according to claim 7, characterized in that: The carbon-zeolite composite material is used to adsorb ammonia nitrogen compounds in wastewater and catalytically degrade refractory organic matter in water. The specific method is as follows: Add 5-10 g / L of gasification slag-based carbon-zeolite composite material to wastewater containing ammonia nitrogen and refractory organic matter, then add 1-1.5 g / L of oxidant, and perform adsorption catalysis at room temperature for 70-90 minutes; The oxidant is sodium persulfate or potassium persulfate.
Citation Information
Cited By
Gasification slag-based porous geopolymer / g-C3N4 heterojunction photocatalytic microspheres as well as preparation method and application thereof
CN121222468A
A porous geopolymer / g-C3N4 heterojunction photocatalytic microsphere based on gasification slag, its preparation method and application
CN121222468B
Gasification slag-based composite phase hierarchical pore channel photocatalytic material as well as preparation method and application thereof
CN121244267A
Gasification slag-based composite phase multi-level porous photocatalytic materials, their preparation methods and applications
CN121244267B